Dense multilayer metamaterial absorbers for Ka-band satellite frequency applications - Tayaallen Ramachandran,; Mohammad Rashed Iqbal Faruque*, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This work investigates the effects of multi-layered metamaterial design for absorption application at satellite frequency. This is because, the adopted Ka-band frequency is very useful for current technology which can be used in high-resolution, close-range targeting radars, military aircraft, space telescopes, commercial, and wireless point-point microwave communication systems. Hence, this work focused on producing a compact design by adopting the optimisation method. Four square-shaped and two circular-shaped metamaterial rings were designed on 0.25 mm substrate material. Furthermore, the properties of the proposed metamaterial were discovered by adopting Computer Simulation Technology. This analytical simulation was performed for a frequency range between 27 and 40 GHz. On the other hand, several design analyses were investigated to gain an optimal metamaterial design structure for the proposed applications. For instance, unit cell selection analysis, reflection coefficient and absorbance analysis of the multi-layer metamaterial. Moreover, the proposed unit cell metamaterial manifests double resonance frequencies for reflection and transmission coefficients approximately at 27.31 GHz, 33.40 GHz and 30.56 GHz, 38.23GHz, respectively. The increment of layers on the proposed unit cell structure revealed unique responses. For example, the double multi-layer metamaterial manifests similar dual resonance frequencies as the unit cell design but gains excellent magnitude values of more than -10. Moreover, the absorbance of the three distinct layer metamaterials, likely double, triple and quadruple layers were analysed as well in this work. Overall, the proposed compact metamaterial absorber exhibits unique behaviours for Ka-band satellite frequency applications.